Enhancing Community Capacity through a Workshop on Diversification and Innovation of Seaweed Nastar Products - Iftachul Farida; Anis Khairunnisa; I Made Aditya Nugraha; I Gusti Ayu Budiadnyani; Siluh Putu Sri Dia Utari; I Ketut Sumandiarsa; Ika Astiana; Pinky Natalia Samanta; Resti Nurmala Dewi; Fenny Crista Anastasia Panjaitan; Mahaldika Cesrany; Medal Lintas Perceka; Tri Audia Paputungan; Dwi Adinda Wulan Maulidiyah; Ni Luh Dea Sari (Universitas Muhammadiyah Palembang, 2026)
Eucheuma cottonii seaweed is a key Indonesian fishery commodity with significant potential for development into value-added food products. However, its utilization by the community remains relatively limited, necessitating empowerment efforts through product diversification. This community service activity aimed to enhance the community's knowledge and skills in processing seaweed into nastar (pineapple tarts) and to foster an entrepreneurial spirit rooted in marine resources. The activity was conducted as a workshop involving the Wijaya Fish group, students, lecturers, and online participants from various institutions. The methods employed included material presentation, demonstrations, hands-on nastar making, business analysis, and evaluation using pre-tests, post-tests, and satisfaction questionnaires. Evaluation results showed an increase in the average score from 9.6 in the pre-test to 10.0 in the post-test; however, the Wilcoxon test indicated that this increase was not statistically significant (p > 0.05), likely due to the participants' high baseline knowledge and the limited number of respondents. The satisfaction evaluation yielded an average score of 4.04 (categorized as good), with the practical demonstration being the aspect most appreciated by participants. Overall, the workshop successfully improved participants' understanding, skills, and motivation regarding the development of value-added seaweed products. This initiative has the potential to support fishery product diversification, enhance the competitiveness of MSMEs, and encourage the sustainable utilization of marine resources